Impact of COVID-19 on the Mental Health of Medical Students of Karachi, Pakistan - Fareena Khalil Ahmed, Hr Sukhia, Rabia Ejaz, Qurat-Ul-Ain Khan, Ujala Mushtaque, Saher Mushtaque (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The biggest dilemma of today’s world is COVID-19. This pandemic situation has completely engulfed the globe with a rapidly increasing number of cases and has affected a great number of lives along with their lifestyle including the educational sector. Objective: This study explores the impact of COVID-19, how frequent lockdown, and online learning have affected the mental health of the students of medical college. Methods: A cross-sectional study was conducted among the medical students of Karachi, in September 2021, in Jinnah Medical and Dental College. A total of 312 medical students were enrolled in the study. Out of which 208 were females and 104 were males. Depression Anxiety Stress Scale-21 (DASS-21) was used to assess the mental health of students of medical college. Results: The results of the study revealed that a total of 312 medical students were enrolled in the study; belonging to the age group of (18-25) years. Approximately 104 (66 %) of female students experienced depression, 44 (21%) anxiety, and 60 (28%) stress. Hence gender and year of study of the participants were found to be significant (p-value<0.05). The odds of first-year students showed high levels of anxiety as compared to final-year students (OR = 1.679, 95% CI [1.202–2.634], P = 0.002). Conclusion: This study will help in making relevant policies, mental health strategies and providing a better framework for the medical colleges and universities which is essential for the mental health of students.